ЗНАЧЕННЯ ДОПОМІЖНИХ МАТЕРІАЛІВ ТА ТЕХНІК АКВАРЕЛЬНОГО ЖИВОПИСУ ПРИ ВИКОНАННІ СТУДЕНТАМИ ТВОРЧИХ ЗАВДАНЬ НА АКАДЕМІЧНИХ ТА САМОСТІЙНИХ ЗАНЯТТЯХ (Педагогіка вищої та середньої школи, 2006)
Value of auxiliary materials and mechanic: water colour painting al performaner by studets of creative tasks on the academic aid independent occupations. In the article arc examined the problem of perfecting the instruction of students, who learned on first counts of the artisncally-graphic faculties, to the water-color painting at the special course "Technology of the water-color painting".